An osteological study of morphometry of hard palate and its importance - KL, Varalakshmi; M, Sangeeta; Naik, Shilpa N.; Acharya, Arunashri (International Journal of Research in Medical Sciences, 2017)
Background: The hard palate is an essential part of human skull, the detailed knowledge of which plays an important role in the passive articulation of speech. Methods: The present study was conducted on 65 dry skulls from the department of anatomy, MVJMC & RH, Bangalore. With vernier caliper, palatine length, palatine breadth and heights were measured. Palatine index and palatine height index were calculated. Results: Mean palatine length was 48.47 ± 4.66 mm. Mean palatine breadth was 36 ± 4.41 mm and height was 8.62 ± 2.76 mm. According to the palatine index range, 66% of the hard palate belongs to leptostaphyline, 18.5% belongs to mesostaphyline and 15. 5% was brachystaphyline. As per palatine height index, 72.3% of hard palate showed chamestaphyline followed by 26.1% orthostaphyline and 1.6% hypistaphyline. Conclusions: These observations can be utilised for ethnic and racial classification of crania, anthropological studies, fabricating complete maxillary dentures for edentulous patients and performing certain surgical procedures in hard palate & soft palate.